Pinpointing the ‘cinematic’ in twenty-first century art: ‘Dreamlands’ / ‘On desire’ - Chinita, Fátima (2020)
Book review of two exhibition catalogues with additional texts: Iles, Chrissie (ed.), Dreamlands (New York: Whitney Museum of American Art, 2017) and Kracke, Bernd and Marc Ries (eds.), On Desire (Bielefeld: Transcript Verlag, 2017).